Self‐Assembled Polymeric Ionic Liquid‐Functionalized Cellulose Nano‐crystals: Constructing 3D Ion‐conducting Channels Within Ionic Liquid‐based Composite Polymer Electrolytes. Issue 49 (9th August 2017) - Shi, Qing Xuan; Xia, Qing; Xiang, Xiao; Ye, Yun Sheng; Peng, Hai Yan; Xue, Zhi Gang; Xie, Xiao Lin; Mai, Yiu‐Wing
Abstract: Composite polymeric and ionic liquid (IL) electrolytes are some of the most promising electrolyte systems for safer battery technology. Although much effort has been directed towards enhancing the transport properties of polymer electrolytes (PEs) through nanoscopic modification by incorporating nano‐fillers, it is still difficult to construct ideal ion conducting networks. Here, a novel class of three‐dimensional self‐assembled polymeric ionic liquid (PIL)‐functionalized cellulose nano‐crystals (CNC) confining ILs in surface‐grafted PIL polymer chains, able to form colloidal crystal polymer electrolytes (CCPE), is reported. The high‐strength CNC nano‐fibers, decorated with PIL polymer chains, can spontaneously form three‐dimensional interpenetrating nano‐network scaffolds capable of supporting electrolytes with continuously connected ion conducting networks with IL being concentrated in conducting domains. These new CCPE have exceptional ionic conductivities, low activation energies (close to bulk IL electrolyte with dissolved Li salt), high Li + transport numbers, low interface resistances and improved interface compatibilities. Furthermore, the CCPE displays good electrochemical properties and a good battery performance. This approach offers a route to leak‐free, non‐flammable and high ionic conductivity solid‐state PE in energy conversion devices. Abstract : A 3D self‐assembled polymeric ionic liquid (PIL)‐functionalized cellulose nano‐crystals confining ILs in surface‐grafted PIL brushes, able to form colloidal crystal polymer electrolytes (CCPE), is prepared that can be employed for high performance Li‐ion battery. CCPE have exceptional ionic conductivities, low activation energies, high Li + transport numbers, low interface resistances, improved interface compatibilities, good electrochemical properties and a good battery performance.